2014
DOI: 10.1155/2014/251479
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of IL-6, IL-8/CXCR2 Axis,Tyrp-STAT-3, and SOCS-3 in Lymph Nodes from Patients with Chronic Lymphocytic Leukemia: Correlation between Microvascular Characteristics and Prognostic Significance

Abstract: A number of studies have looked into the pathophysiological role of angiogenesis in CLL, but the results have often been inconsistent. We aimed to gain direct insight into the angiogenic process in lymph nodes involved by CLL, focusing on proangiogenic cytokines and microvessel morphometry. The tissue levels of VEGF, Th-2 cytokines IL-6 and IL-8, IL-8 receptor CXCR2, and tyrosine p-STAT-3/SOCS-3 axis modulating cytokine expression were evaluated immunohistochemically in 62 CLL/SLL cases. Microvascular characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 59 publications
5
13
0
Order By: Relevance
“…Consistent with the literature, the basal STAT3 phosphorylation on Tyr705 increased when CLL cells were co-cultured on BMSC layers or incubated with IL-6. In addition, Levidou et al recently reported that STAT3 is constitutively phosphorylated at Tyr705 in CLL cells resident in lymph nodes [44].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the literature, the basal STAT3 phosphorylation on Tyr705 increased when CLL cells were co-cultured on BMSC layers or incubated with IL-6. In addition, Levidou et al recently reported that STAT3 is constitutively phosphorylated at Tyr705 in CLL cells resident in lymph nodes [44].…”
Section: Discussionmentioning
confidence: 99%
“…37 Immunohistochemistry also detects IL-6 in most CLL lymph nodes. 38 Evidence that CLL cells encounter IL-6 in PCs is suggested by microarray studies that demonstrate increased expression of the IL-6 signature gene IL4RA by recent emigrants to the circulation. 39,40 Published gene-array data also suggest TLR7 is decreased when CLL cells enter lymph nodes 41 (supplemental Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…24 Although these stimuli may not be operating in vivo, IL-10 transcript is upregulated within CLL cells of the lymph node, 69 and STAT3, a potent mediator of IL-10-driven antiinflammatory signaling, 85 is also phosphorylated in the tissues of CLL patients. [86][87][88] The key determinants in vivo that drive the differentiation of CLL cells from a B10pro cell state into an effector B10 cell state are not yet clear. 80 Mice models indicate that prior antigen exposure is required for proper differentiation into B10 cell, 89 but it is likely that the strength of signaling through the BCR is another key factor.…”
Section: Role Of Cll Cells In Mediating Immune Suppression: the Tumormentioning
confidence: 99%